Effectiveness of topical oxygen therapy in wound healing for patients with diabetic foot ulcer - Queg Marvin; De Leon Josephine (Sciendo, 2023)
Objectives: Non-healing wounds have been one of the major challenges in health care because of increased morbidity, especially for those who have diabetes mellitus. Numerous regimens are being innovated to produce an evidence-based practice that would minimize complications and promote healing. Topical oxygen therapy is an innovation in wound care that has been considered influential in the wound healing process. This intervention aims to increase the oxygen concentration in the affected limb to promote wound healing.